The Prognostic Value of the Proliferation Marker Phosphohistone H3 (PPH3) in Luminal, Basal-Like and Triple Negative Phenotype Invasive Lymph Node-Negative Breast Cancer - Ivar Skaland; Emiel A. M. Janssen; Einar Gudlaugsson; Lydia Hui Ru Guo; Jan P. A. Baak (Cellular Oncology)
Purpose: Prognostic comparison of phosphohistone-H3 (PPH3) with Cytokeratin 5/6 and/or 14 positive (= basal-CK), triple (ER, PR, HER2)-negative (= TNP) and basal-like (= TNP and basal-CK positive) phenotype in invasive breast cancers.